Perfil epidemiológico dos atendimentos antirrábicos humanos pós-exposição no município de Santa Maria, RS, Brasil - Vasconcellos, Jaíne Soares de Paula (2017)
Rabies is a viral zoonosis that presents progressive and lethal development in almost 100% of cases. Besides being a disease of great importance for the costs generated in livestock and human rabies treatments. The objective of this study was to define the epidemiological profile of human rabies in the municipality of Santa Maria, Rio Grande do Sul, Brazil, from 2010 to 2015. Data from the Notification of Invalidity Information System (Sistema de Informação de Agravo de Notificação, SINAN) were obtained. Through the completion of individual records of human rabies cases (ICD10-W64). The data were analyzed with the aid of the Tabwin® program and later exported to the Excel® program, forming a database that was organized and analyzed using R® software. Thus, post-exposure rabies treatments occurred in 55.0% of the cases in females and 45.0% in males. The highest occurrence (54.5%) was observed in the age group from 20 to 59 years. Mainly, 87.5% of registered cases were caused by canine and 10.9% feline animals. The site of exposure that obtained the highest number of attacks by canine bite was the lower limb with 22.1%. It was possible to observe indications of precipitated treatments, both in cases of indirect contacts and in cases in which the animals were healthy, observable and negative clinically or laboratorially for the disease. There was a large number of fields contained in the mandatory notification form which were ignored at the time of filling. It is suggested a program for training of the professionals involved with this aggravation and the dissemination of information aimed an instrumentalizing for the users about the accidents. An informative folder containing the main information to be transmitted to the residents was developed. In addition, a flow chart was drawn up guiding the actions against the anti-rabies visits to be applied in the city.